Insecurity in an Orange Envelope: National Pension System Reform in Sweden. Issue 2 (November 2015) - Nyqvist, Anette
Abstract : In this article, I examine the implications of Sweden's reformed national pension system and how this policy reconfigures the state–citizen relationship. By applying the methodological approach of "studying through, " the study depicts a shift in responsibility from a state level to an individual level. More specifically, I here shed light on how politicians, technocrats, and bureaucrats work to educate and foster the general public into responsible, hard working and financially literate citizens. The article further reveals that such attempts are not readily accepted or adopted by the citizens at the receiving end of the pension policy and so, instead of providing stability and security, this social security policy invokes a sense of insecurity in Swedish citizens . [Pension System Reform, Anthropology of Policy, Sweden, Studying Through]